Audit Committee and Value Relevance of Public Company in Indonesia - Lely Kumalawati; Vaisal Amir; Halleina Rejeki Putri Hartono (AKRUAL: JURNAL AKUNTANSI, 2025)
Background: The role of audit committees in corporate governance has garnered significant attention in modern financial practices, especially regarding their influence on the value relevance of public companies. Objectives: This study aims to examine the moderating effect of audit committees in strengthening the value relevance of financial statements in predicting stock prices. Methods: The population of this study is all companies listed on the Indonesia Stock Exchange (IDX). The research period will be conducted for 24 years, from 2001 to 2024. Data analysis will be conducted using a statistical approach consisting of descriptive statistics, classical assumption tests, model feasibility tests, and research hypothesis tests. The hypothesis testing process in this study is carried out using causal step OLS testing. This study will use a 95% confidence level and a one-tailed test. Results: The results showed that cash, inventory, liabilities, company size, and company age were able to predict company value through earnings per share, but receivables were not able to predict company value through earnings per share. Furthermore, the study failed to find any effect of audit committee size in predicting company value through earnings per share, and there was no empirical evidence regarding its role in strengthening the value relevance of financial information in predicting earnings per share.